2012
DOI: 10.1016/j.pbb.2011.11.013
|View full text |Cite
|
Sign up to set email alerts
|

Effects of GABA ligands injected into the nucleus accumbens shell on fear/anxiety-like and feeding behaviours in food-deprived rats

Abstract: In an attempt to establish a relationship between food intake and fear/anxiety-related behaviours, the goal of this study was to investigate the effect of bilateral injections of GABAA (Muscimol, MUS, doses 25 and 50ng/side) and GABAB (Baclofen, BAC, doses 32 and 64ng/side) receptor agonists in the nucleus accumbens shell (AcbSh) on the level of fear/anxiety-like and feeding behaviours in 24h food-deprived rats. The antagonists of GABAA (Bicuculline, BIC, doses 75 and 150ng/side) and GABAB (Saclofen, SAC, dose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 56 publications
2
10
0
Order By: Relevance
“…These results suggest that the UCMS has effectively contributed in the development of anxiety in animals. This result has also been reported by Frih et al [ 26 ] and may be due to the inhibitory activity of the GABAergic system [ 43 ]. On the other hand, the treatment of anhedonic rats with F. sycomorus extracts significantly reduced the number of entries in the closed arms (100 and 200 mg/kg, p < 0.001) and the number of time spent in the closed arms (100 mg/kg, p < 0.05).…”
Section: Discussionsupporting
confidence: 88%
“…These results suggest that the UCMS has effectively contributed in the development of anxiety in animals. This result has also been reported by Frih et al [ 26 ] and may be due to the inhibitory activity of the GABAergic system [ 43 ]. On the other hand, the treatment of anhedonic rats with F. sycomorus extracts significantly reduced the number of entries in the closed arms (100 and 200 mg/kg, p < 0.001) and the number of time spent in the closed arms (100 mg/kg, p < 0.05).…”
Section: Discussionsupporting
confidence: 88%
“…Hyperactivity in the form of increased locomotion has been reported in studies using disinhibition of limbic territories in rats, including the NAc (Wachtel and Andén, 1978;Jones et al, 1981;Morgenstern et al, 1984) and the ventral pallidum (Mogenson and Nielsen, 1983;Austin and Kalivas, 1990), and in primates (Worbe et al, 2009). In addition, disinhibition of the NAc shell led to emotional dysregulation (Stratford and Kelley, 1997;Lopes et al, 2012), which may contribute indirectly to the observed changes in locomotion. Multiple different hyperkinetic states have been evoked using similar manipulations in the sen-sorimotor basal ganglia: disinhibition of the sensorimotor striatum leads to motor tics (Tarsy et al, 1978;McCairn et al, 2009;Bronfeld et al, 2013;Pogorelov et al, 2015;Klaus and Plenz, 2016), downstream disinhibition in the sensorimotor GPe leads to chorea (Grabli et al, 2004;Bronfeld et al, 2010) and disinhibition of the striatum in cats (Yamada et al, 1995), and the motor thalamus in primates (Guehl et al, 2000) leads to dystonia.…”
Section: Discussionmentioning
confidence: 99%
“…The varied results of the present study from those of other studies may be related to the procedure of study. Saclofen, as GABA B antagonist, injection in nucleus accumbens shell did not affect the fear/anxiety behaviors (Lopes et al, 2012). 2-OH saclofen blocked the inhibitory effects of serotonin in the lateral amygdala: as a mechanism for modulation of sensory inputs related to fear conditioning (Stutzmann and LeDoux, 1999).…”
Section: Discussionmentioning
confidence: 87%
“…Activation of GABA B receptor in the nucleus accumbens shell decreased the level of fear/anxiety, without a positive correlation between these behaviors (Lopes et al, 2007). Lopes et al (2012) reported that the activation of both GABA A and GABA B receptors within the AcbSh can cause fear/anxiety behavior in 24 h food-deprived rats as demonstrated by this fact that the injections of both doses of the GABA A receptor agonist (muscimul) and GABA B receptor agonist (baclofen) decreased the total number of risk assessment exhibition in 24 h fooddeprived rats (Lopes et al, 2012). In the present study, CGP35348 had no effect on the frequency of fear response in rats without exposure to EMF.…”
Section: Discussionmentioning
confidence: 99%